Combinatorial readout of histone H3 modifications specifies localization of ATRX to heterochromatin. - Eustermann, S; Yang, J; Law, M; Amos, R; Chapman, L; Jelinska, C; Garrick, D; Clynes, D; Gibbons, R; Rhodes, D; Higgs, D; Neuhaus, D (Nature Publishing Group, 2011)
Accurate read-out of chromatin modifications is essential for eukaryotic life. Mutations in the gene encoding X-linked ATRX protein cause a mental-retardation syndrome, whereas wild-type ATRX protein targets pericentric and telomeric heterochromatin for deposition of the histone variant H3.3 by means of a largely unknown mechanism. Here we show that the ADD domain of ATRX, in which most syndrome-causing mutations occur, engages the N-terminal tail of histone H3 through two rigidly oriented binding pockets, one for unmodified Lys4 and the other for di- or trimethylated Lys9. In vivo experiments show this combinatorial readout is required for ATRX localization, with recruitment enhanced by a third interaction through heterochromatin protein-1 (HP1) that also recognizes trimethylated Lys9. The cooperation of ATRX ADD domain and HP1 in chromatin recruitment results in a tripartite interaction that may span neighboring nucleosomes and illustrates how the 'histone-code' is interpreted by a combination of multivalent effector-chromatin interactions.